Efficient TTI for 3G Multimedia Applications - Costas Chaikalis (Advances in Multimedia)
Time transmission interval (TTI) or outer block interleaving is an important task for the implementation of UMTS turbo coding in flat Rayleigh fading environment. An efficient TTI choice can save computational complexity. However, different multimedia scenarios are investigated using the maximum UMTS frame length, and simulation results are presented for the four possible outer block interleaver configurations in the case of flat Rayleigh fading channel. It is shown that different operating environments require an appropriate TTI in terms of bit error rate (BER) performance for the following data rates: 28.8 kbps, 64 kbps, 144 kbps, 384 kbps, and 2 Mbps.